Myocardial protection and clinical outcomes in Tetralogy of Fallot patients undergoing intracardiac repair: a randomized study of two cardioplegic techniques. (September 2019) - Negi, Sunder Lal; Mandal, Banashree; Singh, Rana Sandeep; Puri, Goverdhan Dutt
Background: Myocardial protection in Tetralogy of Fallot patients undergoing intracardiac repair is suboptimal due to hypertrophied right ventricle. Hypertrophied myocardium is more susceptible to poor myocardial preservation because of inadequate capillary density as compared to the myocytes. There is a capillary to myocyte ratio mismatch. But del Nido Cardioplegia owing to its less viscosity is able to get more evenly distributed under hypothermic cardiopulmonary bypass as opposed to blood Cardioplegia. We hypothesized that the del Nido Cardioplegia technique, would be beneficial in myocardial protection because of its composition and method of delivery, leading into better early and late clinical outcomes in patients undergoing Tetralogy of Fallot repair as compared to blood cardioplegia reconstituted using St Thomas Cardioplegia solution. The objective of the study was to identify a better technique of myocardial preservation in Tetralogy of Fallot patient. Methods: In total, 56 Tetralogy of Fallot patients undergoing intracardiac repair under mild hypothermic cardiopulmonary bypass were randomly allocated to receive antegrade Cardioplegia with either standard blood Cardioplegia (Group I) or del Nido Cardioplegia (Group II). Preoperative as well as postoperative data including echocardiographic parameters for right ventricle functions, creatine kinase MB level, inotropic requirement, mechanical ventilation duration, intensive care unit stay and hospital mortality were evaluated. Results: Inotropic score in the first 24 hours postoperatively was significantly lower in Group II compared to Group I (13.4 ± 7.2 vs. 21.2 ± 9.6, p = 0.003). Creatine kinase MB level (ng/mL) was comparable between the groups. Echocardiographic parameters for right ventricle functions were also comparable between the groups during early as well as after 3 to 6 months postoperatively. Conclusion: Del Nido Cardioplegia is equally efficacious in providing myocardial protection during intracardiac repair under mild hypothermic cardiopulmonary bypass in Tetralogy of Fallot patients as compared to blood Cardioplegia solution with the added benefit of reducing inotropic requirement in first 24 hours postoperative period.